Oriented growth of Blastocladiella emersonii in gradients of ionophores and inhibitors. - Harold, R L (1980)
To investigate whether ion currents help to localize growth and development of Blastocladiella emersonii, we grew the organisms in gradients of various ionophores and inhibitors. Gradients were generated by placing into the culture fine glass fibers coated with insoluble inhibitors; in some cases, inhibitors were adsorbed onto beads of ion-exchange resin. Organisms growing in many of these gradients exhibited a striking tendency for the thalli to grow toward the fiber. This proved to be misleading; the cells grew not toward the source of the ionophore but into the unoccupied zone of inhibition adjacent to the fiber. Fibers coated with gramicidin-D induced marked effects on the growth of the rhizoids, which were greatly enlarged and grew toward and onto the fiber. None of the other inhibitors produced such effects, except for beads coated with the proton conductors tetrachlorosalicylanilide and compound 1799. The results suggest that orientation of rhizoid growth results from enhancement of proton flux across the plasma membrane. Growth of the rhizoids was also strongly oriented by gradients of inorganic phosphate and an amino acid mixture; gradients of glucose, K+, Ca2+, and glutamate were ineffective. We propose that a major physiological function of the rhizoid is to transport nutrients to the thallus. Finally, we examined the effects of a series of benzimidazole antitubulins as well as the cytochalasins. These did not orient growth but grossly perturbed the pattern of cellular organization, producing small spherical cells with multiple stunted rhizoids. The findings are interpreted in terms of the interaction of an endogenous transcellular proton current with elements of the cytoskeleton in the determination of form.